2017
DOI: 10.1111/micc.12390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different‐intensity laser acupuncture at two adjacent same‐meridian acupoints on nitric oxide and soluble guanylate cyclase releases in human

Abstract: This is the first evidence reporting that LA induced significant elevations of NO-sGC releases over acupoints, and the enhanced signal molecules contribute to local circulation, which improves the beneficial effects of the therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 36 publications
(83 reference statements)
2
13
0
Order By: Relevance
“…There is a linear relationship between the absorbance and concentrations of nitrobenzene/protein [ 18 , 19 ]; in our research, we have also demonstrated that the linear relationship between absorbance and NO 3 − /NO 2 − concentrations at 302/351 nm peaks as shown in Figures 2(a) and 2(b) (ND-1000, NanoDrop spectrophotometer, Gene Company Limited). LA at PC6, nonacupoint for 40 minutes, produced typical three peaks of absorbance spectra in PTIO solution which was injected to special silicon tube placed on PC6 just after LA treatment ( Figure 3 ) [ 4 ]. Based on the previous studies, the first (235 nm) and second (351 nm) peaks came from NO x − [ 20 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a linear relationship between the absorbance and concentrations of nitrobenzene/protein [ 18 , 19 ]; in our research, we have also demonstrated that the linear relationship between absorbance and NO 3 − /NO 2 − concentrations at 302/351 nm peaks as shown in Figures 2(a) and 2(b) (ND-1000, NanoDrop spectrophotometer, Gene Company Limited). LA at PC6, nonacupoint for 40 minutes, produced typical three peaks of absorbance spectra in PTIO solution which was injected to special silicon tube placed on PC6 just after LA treatment ( Figure 3 ) [ 4 ]. Based on the previous studies, the first (235 nm) and second (351 nm) peaks came from NO x − [ 20 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed the standard molecules under the same conditions to confirm this speculation. We have discovered that the first peak at 235 nm and the second peak at 351 nm all came from NO 2 − (Figures 2(a) and 2(b) ) [ 4 ]. Additionally, the NO 2 − absorbance at 235 nm was easily saturated; thus, absorbance peak at 351 nm was used to evaluate the levels of NO trapped by PTIO solution [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations